(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
This present study aimed to perform a histological comparison of the liver in three types of vertebrates: Hyla savignyi, Hemidactylus turcicus, Testudo graeca. The results showed a structural similarity of the liver in the previous animals, with significant differences in the place of hepatic cells and sinusoids and the presence of the hepatic triad, furthermore, it has been observed that hepatic cells are placed as glomeruli in the liver of Hyla savignyi, and glomerular reticular in Hemidactylus turcicus; on the other hand, the hepatic cells in Testudo graeca are placed in format of glomerular corded around the central vein. moreover, The study also revealed the absence of hepatic triad in both Hemidactylus turcicus and Hyla savignyi ; Testudo graeca, in contrast, have hepatic triad. هدفت الدراسة الحالية إلى إجراء مقارنة نسيجية للكبد عند ثلاثة أنواع من الفقاريات: ضفدع الشجر Hyla savignyi، أبو بريص البحر المتوسط المنزلي Hemidactylus turcicus، السلحفاة مهمازية الورك Testudo graeca. أظهرت النتائج تشابهاً بنيوياً للكبد عند حيوانات الدراسة، مع وجود اختلافات ملحوظة في توضع الخلايا الكبدية والجيبانيات (أشباه الجيوب) ووجود الثالوث الكبدي، حيث لوحظ توضع الخلايا الكبدية بشكل كبيبات في كبد الضفدع، وكبيبي شبكي عند أبو بريص، أما عند السلحفاة فتتوضع الخلايا الكبدية بشكل كبيبي حبلي حول الوريد المركزي. كما كشفت الدراسة غياب الثالوث الكبدي عند أبو بريص وضفدع الشجر مقارنة مع السلحفاة مهمازية الورك.